Peptide Analysis Protocols - Dunn, Ben M.; Pennington, Michael W. (Methods in Molecular Biology, 1994)
As the technology base for the preparation of increasingly c- plex peptides has improved, the methods for their purification and ana- sis have also been improved and supplemented. Peptide science routinely utilizes tools and techniques that are common to organic chemistry, p- tein chemistry, biophysical chemistry, enzymology, pharmacology, and molecular biology. A fundamental understanding of each of these areas is essential for interpreting all of the data that a peptide scientist may see. The purpose of Peptide Analysis Protocols is to provide the novice with sufficient practical information necessary to begin developing useful analysis and separation skills. Understanding and developing these skills will ultimately yield a scientist with broadened knowledge and good problem-solving abilities. Although numerous books that address d- ferent specialties, such as HPLC, FAB-MS, CE, and NMR, have been written, until now no single volume has reviewed all of these techniques with a focus on "getting started" in separation and analysis of peptides. This volume will also provide those who already possess practical knowledge of the more advanced aspects of peptide science with detailed applications for each of these protocols. Because the chapters have been written by researchers active in each of the fields that they discuss, a great deal of information on and insight into solution of real problems that they have encountered is presented. Examplary results are clearly demonstrated and discussed. For more advanced investi- tions, supplementary experiments are often suggested